2018
DOI: 10.4236/oalib.1104854
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Delay Optimization and Workload Assignment in Mobile Edge Cloud Networks

Abstract: Nowadays, the usage of mobile devices is progressively increased. Until, delay sensitive applications (Augmented Reality, Online Banking and 3D Game) are required lower delay while executed in the mobile device. Mobile Cloud Computing provides a rich resource environment to the constrained-resource mobility to run above mentioned applications, but due to long distance between mobile user application and cloud server introduces hybrid delay (i.e., network delay and process delay). To cope with the hybrid delay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…A.Rasheed et al, Lixing et al and Dileep et al [10][11][12] proposed dynamic programmingbased iterative and full approximation methods based on Lyapunov optimization heuristics to solve the workload assignment problem in the distributed edge cloud network. The concave and convex optimization-based solution suggested solving the travelling salesmen's problem for workload in the network.…”
Section: Related Workmentioning
confidence: 99%
“…A.Rasheed et al, Lixing et al and Dileep et al [10][11][12] proposed dynamic programmingbased iterative and full approximation methods based on Lyapunov optimization heuristics to solve the workload assignment problem in the distributed edge cloud network. The concave and convex optimization-based solution suggested solving the travelling salesmen's problem for workload in the network.…”
Section: Related Workmentioning
confidence: 99%
“…The study [6] investigated scheduling problem for daily-check-system and submitted distributed fog cloud medical care network. The goal was to minimize cost and tardiness of the applications.…”
Section: Related Workmentioning
confidence: 99%
“…Many healthcare monitoring system suggested to offer different services to the patients. Many existing studies [6][7][8][9][10] suggested different pricing model for healthcare applications such as E-Blood-Pressure, E-Blood Analysis, EEG, and ECG and so on. Every provider rent services based on different pricing model such as on-demand, on-reserve, and spot-instants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, we arrange the offloaded tasks into the topological order by the known sorting algorithm [19]. Furthermore, each task has a set of vector attributes such as data size, required CPU instruction, and deadline.…”
Section: A Proposed Microservices Fog-cloud Architecturementioning
confidence: 99%